2022
DOI: 10.1252/jcej.22we031
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Deposition Assisting the Enhancement of Catalytic Activity with Time-on-Stream in the Dehydrogenation of Isobutane over NiO/Al<sub>2</sub>O<sub>3</sub>

Abstract: In the transformation reaction of alkanes in alkenes via catalytic dehydrogenation, it is generally accepted that catalytic deactivation will occur. This phenomenon causes a drastic reduction in the catalytic activity with time-on-stream. It is understood that carbon deposits generated during the reaction then covers the surface of the catalyst, leading to a drastic decrease in activity. However, in contradiction, our laboratory reported that the dehydrogenation of isobutane to isobutene on NiO/γ-Al 2 O 3 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…It has been reported that nickel oxide supported on γ-alumina is reduced to metallic nickel when using hydrogen at temperatures lower than 673 K (Heracleous et al, 2005). In addition, our laboratory also revealed that only metallic nickel was detected with XRD of NiO(20)/γ-Al 2 O 3 recovered a er the dehydrogenation of isobutane at 0.1 h on-stream (Sugiyama et al, 2022). erefore, in the present reaction systems as well, the reduction of NiO to metallic Ni is expected to proceed in the early stages of each dehydrogenation.…”
Section: Reduction Of Nio To Metallic Ni At Initial Time-onstreamsupporting
confidence: 58%
“…It has been reported that nickel oxide supported on γ-alumina is reduced to metallic nickel when using hydrogen at temperatures lower than 673 K (Heracleous et al, 2005). In addition, our laboratory also revealed that only metallic nickel was detected with XRD of NiO(20)/γ-Al 2 O 3 recovered a er the dehydrogenation of isobutane at 0.1 h on-stream (Sugiyama et al, 2022). erefore, in the present reaction systems as well, the reduction of NiO to metallic Ni is expected to proceed in the early stages of each dehydrogenation.…”
Section: Reduction Of Nio To Metallic Ni At Initial Time-onstreamsupporting
confidence: 58%
“…An EXSTAR6000 (Seiko Instruments Inc.) under air flow (100 mL/min) at a heating rate of 8 K/min from 298 to 1073 K was employed for thermogravimetric (TG) analysis. According to our previous studies 5), 6) , the amount of carbon deposited on the catalyst after the reaction was estimated as the weight loss obtained using TG to determine the amount of carbon deposited per 1.0 g of fresh catalyst or per 1.0 g of NiO supported on the fresh catalyst (Carbon deposition rate: CDR). A transmission electron microscope (TEM, JEM-2100F, JEOL Ltd.) was used to analyze the catalysts previously used for dehydrogenation.…”
Section: Characterizationmentioning
confidence: 99%